Impact of yeast selection on composition of vinegar fermented from pomace of a Finnish apple cultivar - Wang, Qizai; Laaksonen, Oskar; Xifre Pujol, Elsa; Heinonen, Maarit; Yang, Baoru; Kelanne, Niina (Elsevier, 2024)
Alcoholic beverages and vinegar products were produced using the pomace of a Finnish apple cultivar, and the influence of yeast strains on the non-volatile and volatile compound contents were studied. Apple pomace mashes were fermented with Saccharomyces cerevisiae, Torulaspora delbrueckii, and sequential inoculation with Lachancea thermotolerans and S. cerevisiae to produce alcoholic beverages. Commercial non-pasteurized vinegar was used as a starter to ferment alcoholic beverages into vinegars. Ethanol, acetic acid, sugars and organic acids were determined using GC-FID. A total of 63 volatile compounds were detected in the samples using HS-SPME-GC-MS. Alcoholic beverages fermented with the sequential inoculation had the highest total content of organic acids, and pure inoculation with T. delbrueckii resulted in the highest total content of sugars. Selection of different yeast strains did not alter the content of ethanol or acetic acid, but it significantly influenced the composition of volatile compounds in alcoholic beverages and vinegars. Compared to initial apple pomace mash, significant increases in the contents of ethyl esters (up to 4810-folds), higher alcohols (up to 24-folds) and volatile acids (up to 1853-folds) were observed in fermented products depending on the yeasts used. The main volatile compounds in vinegars prepared from S. cerevisiae fermented beverage were 2-phenylethanol, octanoic acid, and decanoic acid, from T. delbrueckii beverage 2-methylpropanoic acid and 3-methylbutanoic acid, and from sequential fermentation ethyl acetate, and ethyl 2-hydroxypropanoate. In conclusion, non-Saccharomyces yeasts have potential to produce more complex aromatic profile to fermented products derived from by-products of apple juice processing.
Keywords: volatile compounds; apple pomace; acetic acid fermentation; Saccharomyces cerevisiae; Torulaspora delbrueckii; Lachancea thermotolerans